Implantar la contabilidad comercial de la compañía Boris Luis Palomeque y Asociados en la ciudad La Troncal provincia del Cañar, por el período del mes de octubre a diciembre del 2013 - Siguenza Zeas, Karina María (2015)
The main objective in developing the present work is to obtain the title of Engineer in Accounting and Auditing CPA as stipulated in the Regulation of Academic System of the Universidad Nacional de Loja, for which the knowledge acquired during the training was applied in the aforementioned academic institution, which were an important when solving the different situations that crossed contribution. Through the implementation of the accounting process and fulfill the rights objectives that the company is quantified, a Plan and Manual of accounts according to the needs of the company was developed, based on the initial inventory was designed state initial situation with the source documentation commercial transactions in the general journal, general ledger and other accounting records jornalizó up the financial statements, according to the principles and techniques of accounting standards. Financial reasons to analyze the liquidity, solvency and profitability of the Company were applied, which allow the manager to make decisions aimed at growth, investment and capitalization of its assets, in order to achieve greater economic benefits that allow position in the market as a strong and profitable company. We conclude that the process applied I provide real and timely economic and financial information. By which you are advised to Manager of the COMPAÑIA BORIS LUIS PALOMEQUE Y ASOCIADOS exercises this proposal, which will provide an effective tool for proper decision-making and economic growth of the same